Participation in Voluntary Work in Iceland - Hrafnsdóttir, Steinunn; Jónsdóttir, Guðbjörg Andrea; Kristmundsson, Ómar H. (Veftímaritið Stjórnmál og stjórnsýsla, 2014)
The paper discusses participation in formal voluntary work in Iceland. Findings from three waves of the European Values Study (EVS) from 1990-2010 are discussed in a theoretical and international context. The results show that around a third of the Icelandic population aged 18 years and older was involved in some kind of unpaid voluntary work in 2009-2010, a little fewer than in 1990. Around 75% were members of voluntary organizations, about the same ratio as in 1990. Respondents were most likely to do voluntary work for sports- or recreation associations and were also more likely to belong to sports clubs than other associations or organizations. Although voluntary work for social welfare services was the second most frequent, that type of associations suffered the biggest decline in the number of volunteers between 1990 and 2009. Overall, there is not a significant difference in men and women‘s participation in voluntary organizations although men are much more likely than women to do unpaid voluntary work for associations involved in sports, recreation and youth work. Respondents over 50 years are more likely to do voluntary work than younger participants, especially in the field of social welfare. Respondents with higher education are the most likely to be involved in voluntary work. Occupational status is also strongly linked to such work, mainly within sports and recreation. Married respondents are in all instances more likely than others to do voluntary work and people in rural areas are more likely than people in urban areas to engage in such activities. The results that are in accordance with international findings provide important information about participation in voluntary organizations, unpaid voluntary work in Iceland, and changes over time. Í greininni er fjallað um þátttöku Íslendinga í sjálfboðastarfi. Rannsóknin sem byggir á gagnasafni Evrópsku lífsgildakönnunarinnar (EVS) frá 1990-2010 er sett í samhengi við alþjóðlega fræðilega umræðu um sjálfboðaliða og þátttöku í sjálfboðastörfum. Um ...